Perception of Tactile Distance on the Back. (August 2021) - Nicula, Anabela; Longo, Matthew R.
The perceived distance between two touches is anisotropic on many parts of the body. Generally, tactile distances oriented across body width are perceived as larger than distances oriented along body length, though the magnitude of such biases differs substantially across the body. In this study, we investigated tactile distance perception on the back. Participants made verbal estimates of the perceived distance between pairs of touches oriented either across body width or along body length on (a) the left hand, (b) the left upper back, and (c) the left lower back. There were clear tactile distance anisotropies on the hand and upper back, with distances oriented across body width overestimated relative to those along body length/height, consistent with previous results. On the lower back, however, an anisotropy in exactly the opposite direction was found. These results provide further evidence that tactile distance anisotropies vary systematically across the body and suggest that the spatial representation of touch on the lower back may differ qualitatively from that on other regions of the body.